Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.